Contribution of the Implementation of the Independent Campus Learning Program and Student Participation in Campus Intra Organizations to Academic Achievement at State University of Malang - Alvin, Muhammad Khoirul; Juharyanto, Juharyanto; Arifin, Imron; Kusumaningrum, Desi Eri (Proceedings Series of Educational Studies, 2024)
This study aims to analyze the effect of implementing the Merdeka Belajar Kampus Merdeka (MBKM) program and student participation in organizations on academic achievement at the State University of Malang (UM). Using a descriptive quantitative approach and proportionate random sampling technique, 94 respondents from 1,641 students. The results showed: (1) the implementation of the MBKM program at the State University of Malang can be said to be very high with FMIPA as a faculty that has a very high frequency; (2) student participation in organizations at the State University of Malang is in a very high classification with FMIPA as a faculty that shows a very high frequency; (3) the academic achievement of Malang State University students is in a very high classification with FMIPA and FS as faculties that have a very high frequency; (4) MBKM implementation has a positive effect on academic achievement; (5) organizational participation has a negative effect on academic achievement; (6) together, both have a positive effect. Keywords: MBKM program; intra-campus organization; academic achievement